Patient’s safety and satisfaction on same day discharge after robotic and laparoscopic radical prostatectomy versus discharge after 24 or 48 h: a longitudinal randomized prospective study - Faria, Eliney Ferreira; Machado, Roberto Dias; Gualberto, Rodrigo José Costa; Milani, Marina Assunção Valadares; Bidinotto, Lucas Tadeu [UNESP]; Machado, Marcos Tobias; dos Reis, Ricardo; Bidinotto, Daniele Natália Pacharone Bertolini (Springer Nature, 2023)
Background: There is a tendency of prompted global health systems to reduce the length of hospital stay without compromising patient safety or satisfaction. We evaluated the safety and viability of early discharge in patients undergoing minimally invasive radical prostatectomy (MIRP), as well as patient satisfaction with this strategy. Methods: This longitudinal prospective study included 72 patients who underwent MIRP for prostate cancer. Three groups were performed according to the day of hospital discharge following surgery: same day (G1), first day after (G2), and second day after (G3). Satisfaction, adverse events, and readmission were analyzed for each group. Associations between clinicopathologic variables and same-day discharge were analyzed by comparing data between G1 patients who did and did not achieve same-day discharge. Results: 16.7% of patients were not discharged according to randomization (10 randomized to G1). 80% of G1 patients who did not achieve same-day discharge had Gleason scores of 3 + 4 or 4 + 3, which were observed in 35.7% of patients discharged on the same day (P < 0.05). Average prostate weight was significantly lower in patients who achieved same-day discharge than in those who did not (P < 0.01). Univariable logistic regression points to Gleason scores of 3 + 4 or 4 + 3 as the main factors associated with unsuccessful same-day discharge (P < 0.05). There were no significant differences in satisfaction scores. Conclusions: Same-day discharge was both safe and feasible and does not appear to affect satisfaction in a subset of patients with prostate cancer. Surgeons should consider the Gleason score when determining whether same-day discharge is appropriate.
Keywords: Early hospital discharge; Minimally invasive radical prostatectomy; Patient satisfaction; Prostatectomy